Desain Aplikasi Akuntansi UMKM Berdasarkan SAK EMKM Berbasis Microsoft Excel (Studi Kasus Pada UMKM Mawaddah Cosmetics Manado) - Opa Mustopa; Shane Anneke Pangemanan; Ruhiyat Ruhiyat (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Negeri Manado, 2022)
Micro, Small and Medium Enterprises (EMKM) have an important and strategic role for national economic growth, including regional development, job creation and equitable distribution of regional income. For this reason, EMKM is also necessary to apply accounting in accordance with applicable Accounting Standards, namely Financial Accounting Standards. This research aims to assist EMKM in applying accounting in accordance with SAK EMKM by using the Microsoft Excel program. The method used in this research was Research and Development. The data used was collected from the results of interviews with related parties, documents and observations, as well as other supporting data. The interviewees of this research are UKM owners and UKM employees. This research was conducted at UKM Mawaddah Cosmetics Manado. UKM Mawaddah Cosmetics Manado still applies accounting manually and is not in accordance with SAK EMKM. It is recommended, that this UKM should use accounting application program to make financial reports in accordance with SAK EMKM that will simplify the application of accounting and can increase business profits.